A framework of coordination factors affecting design and build projects’ performance in Malaysia / Misbah Mohamed Abdulwahed Ohag - Abdulwahed Ohag, Misbah Mohamed (2022)
The design and build projects (DB) have increased in numbers in the last few decades. DB method is replacing the traditional method, which is becoming more popular in Malaysia, especially in the national projects such as Kuala Lumpur International Airport, Twin Petronas Tower, Penang Bridge, Malaysia North-South Highway. This rapid increase in the DB contracts derived from the urge to avoid the unnecessary cost of traditional projects and to have one team responsible for construction works and designs. However, design-build projects may suffer from a significant number of problems such as conflicts between the project parties (designers, contractors, and owners) resulting poor performance and poor quality. One common cause of project failure of conventional projects is poor coordination and communication process. The DB projects also require proper coordination among stakeholders and in project processes to improve the performance, even though the contractor is responsible for the designs and construction works. It has been found that no such study has been found to identify the coordination factors that might affect the project success. To fill this gap, the aim of this research is to establish a framework of coordination factors affecting DB projects’ performance in Malaysia. In this study, a mixed methodology approach has been utilized to identify critical coordination factors by a comprehensive review of the literature. Additionally, interviews have been conducted to verify and find additional factors from practitioners. The identified factors were then categorized, ranked, and prioritized according to their influence on project performance using a quantitative approach. A Partial Leased Square of Structured Equation Modelling (PLS-based SEM) approach has been applied to identify and estimate the impact of coordination factors on the performance of construction projects in Malaysia. It is found that Scheduling and Planning, Human Resource Coordination, Documentation & Records Coordination, Contract Implementation Coordination, Value Engineering and Quality Assurance, Technical Coordination, Design Coordination, Management Coordination and External Coordination are the major factors of coordination that may affect the performance of construction projects. This study provides empirical evidence by correlating the identified coordination factors with DB project performance. Identification of coordination factors will help in enhancing and improving the performance of design and build projects.